Knowledge and Challenges Associated With Hearing Impairment in Affected Individuals From Cameroon (Sub-Saharan Africa) - Wonkam-Tingang, Edmond; Kengne Kamga, Karen; Adadey, Samuel Mawuli; Nguefack, Seraphin; De Kock, Carmen; Munung, Nchangwi Syntia; Wonkam, Ambroise (Frontiers in Rehabilitation Sciences, 2021)
Background This study aimed to gain an understanding of the challenges faced by people with hearing impairment (HI) in Cameroon, their understanding of the causes of HI, and how challenges could be remedied to improve the quality of life of persons with HI. Methods Semi-structured one-on-one in-depth interviews and observation of participant behaviour when answering questions were used to collect data from 10 HI professionals (healthcare workers and educationists), and 10 persons affected by HI (including caregivers). Results The results show that the different groups associate the causes of HI to genetics, environmental factors, and a spiritual curse. There were reported cases of stigma and discrimination of persons with HI, with people sometimes referring to HI as an “intellectual disorder”. Interviewees also highlighted the difficulty persons with HI have in accessing education and healthcare services and suggested the need for the government and health researchers to develop strategies for the prevention and early diagnosis of HI. These strategies include 1) the awareness of the general population regarding HI, 2) the development of facilities for the proper management and new-born screening of HI, and 3) the implementation of a premarital screening to reduce the burden of HI of genetic origin. Conclusions This study confirms the difficult social interaction and access to proper management faced by persons with HI in Cameroon and further highlights the need to educate populations on the causes of HI for a better acceptance of individuals with HI in the Cameroonian society.